Use of Copper as a Converter Catalyst on Motorcycle Exhaust to Reduce HC (Hidrocarbon) Gas Emissions - Naniek Ratni Juliardi AR; Dimas Hafiiz Wicaksono (International Journal of Eco-Innovation in Science and Engineering, 2020)
The increasing number of vehicles especially in Surabaya means resulting in congestion in light traffic and there are a lot of gas such as CO, CO2, SOx, NOx and HC which produced by motorcycles and other vehicles. It has a big impact for the living things health and needs a specific studies. Copper catalyst design is the most effective in reducing HC motor vehicle gas. The purpose of this study is using a copper catalyst design method that is varied with engine speed (rpm) 1000, 3000, 5000, 8000, type of fuel and using the number of skates 1, 3, 5. The best result of HC gas reduction from the design with skat 5 at rpm 8000 with premium used of 41,5 % from 171 ppm to 100 ppm. This best condition (8000 rpm, 5 skates) uses premium with 88 octan number, pertalite type fuel with 90 octane number, then use the pertamax with 92 octane number. The HC gas results are 6 ppm, 72 ppm and 42 ppm.